Continuous Synthesis of Hydantoins: Intensifying the Bucherer–Bergs Reaction - Monteiro, Julia L.; Pieber, Bartholomäus; Corrêa, Arlene G.; Kappe, C. Oliver (Synlett, 2016)
A continuous Bucherer–Bergs hydantoin synthesis utilizing intensified conditions is reported. The methodology is characterized by a two-feed flow approach to independently feed the organic substrate and the aqueous reagent solution. The increased interfacial area of the biphasic reaction mixture and the lack of headspace enabled almost quantitative conversions within ca. 30 minutes at 120 °C and 20 bar even for unpolar starting materials. In addition, a selective N(3)-monoalkylation of the resulting heterocycles under batch microwave conditions is reported yielding potential acetylcholinesterase inhibitors.
Keywords: continuous flow; process intensification; hydantoins; Bucherer–Bergs reaction; microwave-assisted organic synthesis